Popliteal Fossa Sarcomas - Erdogan, O; Çeli K, A; Yildirim, A. N. T; Tekçe, E; Altun, G; Demi Röz, S; Güler, Y; Ozkan, K; Gurkan, V (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2023)
PURPOSE OF THE STUDY Soft tissue sarcomas of the popliteal fossa are extremely rare tumors of mesenchymal origin accounting for 3%-5% of all extremity sarcomas. However, data regarding the tumor type, neurovascular involvement, and administration of radiation therapy before or after resection are limited. This study aimed to report on popliteal fossa sarcomas analyzing data from two institutions based on a relatively large patient sample. MATERIAL AND METHODS Twenty-four patients (80%; 9 men and 15 women) with a popliteal fossa soft tissue sarcoma were included in this study. The reviewed patient data included sex, age, duration of complaints, interval to diagnosis, radiology, pre- and postoperative biopsy, tumor histology, surgery type, complications, and pre- and postoperative oncologic and functional outcomes. The minimum follow-up was 24 months. RESULTS The mean age of the patients was 48 ± 21.23 (range 3-72) years at the time of diagnosis. The mean follow-up was 41.79 ± 16.97 (range 24-120) months. The most common histological diagnoses were synovial sarcoma (6 patients), hemangiopericytoma (2 patients), soft tissue osteosarcoma (2 patients), unidentified fusiform cell sarcoma (2 patients), and myxofibrosarcoma (2 patients). Local recurrence after limb salvage was observed in six patients (26%). At the latest followup, 2 patients died of the disease, 2 patients were still alive with progressive lung disease and soft tissue metastasis, and the remaining 20 patients were free from the disease. CONCLUSIONS Microscopically positive margins may not be an absolute indication for amputation. Also, negative margins do not provide a guarantee that local recurrence will not occur. Lymph node or distant metastasis may be predictive factors for local recurrence rather than positive margins. Key words: fossa poplitea, sarcoma.
Keywords: Young Adult; Male; retrospektivní studie; Child, Preschool; mladý dospělý; Adolescent; Soft Tissue Neoplasms; Child; dítě; Adult; Aged; dospělí; mužské pohlaví; senioři; sarkom; mladiství; Limb Salvage; předškolní dítě; lidé; ženské pohlaví; Humans; záchrana končetiny; Sarcoma; nádory měkkých tkání; Retrospective Studies; Female; lidé středního věku; Middle Aged